Effect of annealing temperature on microstructure, texture and properties of molybdenum foil. (December 2020) - Fu, Xiaoying; Zhou, Zenglin; Li, Yan; Hui, Zhilin; He, Xueliang; Chen, Wenshuai
Abstract: The microstructure, texture and mechanical properties of 0.06 mm thick molybdenum foil after annealing at different temperatures were studied by micrograph and EBSD analysis. The results show that the grains of the cold-rolled molybdenum foil along the rolling direction are fibrous. As the annealing temperature increasing from 750 °C to 1000 °C, the average layer thickness of these fibrous grains gradually grows. And the relative frequency of low-angle grain boundaries increases, while the relative frequency of high-angle grain boundaries decreases. Also, the main texture of the unidirectional-rolled and annealed molybdenum foils is {112}〈110〉 which content continuously increase to 62% till 1000 °C. Therefore, the strength of RD, TD and 45°RD direction decreases but the elongation increases. During these processes, the mechanism includes classical nucleation and coarsening of subgrain and with annealing temperature rising, the latter dominates the recrystallization process. After annealing at 1050 °C, the molybdenum foil undergoes secondary recrystallization. The grain boundary distribution becomes diffused and the main texture changes into {001}〈110〉, which the fraction is as high as 96%, thus, the mechanical properties of RD, TD and 45°RD exhibit sharp decrease simultaneously. Highlights: The RX behavior and properties of 99.8% reduction of Mo foil were investigated. Elongation in 45°RD reached 50.9%. With annealing temperature rising, the coarsening of subgrain became main mechanism. After secondary recrystallization, the main texture changed into {001}<110>.